Statistical Analysis and Inter- Comparison of Albedo for Athalassa and Larnaca, Cyprus - Pashiardis, Stelios; Kalogirou, Soteris A.; Pelengaris, A. (My University, 2018)
A statistical analysis and inter-comparison of the reflected radiation at two sites in Cyprus representing two different climate regimes of the island (Athalassa-inland plain vs Larnaca-coastal location) covering the period January 2013-December 2015 is presented. Mean annual and mean monthly daily totals of the reflected radiation and ground albedo as well as their frequency distribution are computed and discussed. The monthly means of reflected irradiance range from 50 to 120 W m-2 at Athalassa, while at Larnaca they range between 50 and 140 W m-2. The mean annual albedo for Athalassa is 0.202 which coincides with the most common value given in the literature, while for Larnaca it is higher (0.221). The higher value at Larnaca is attributed to its alluvial (silty sandy) soil which has higher reflectivity compared to the calcarenite (calcium carbonate) soil at Athalassa. The lowest values of albedo at Athalassa, are observed around noon and the higher values in the morning and afternoon. The highest values are obtained in January and February and the lowest in May and June when global solar irradiance have its higher values. On the other hand, we observe an increasing trend from the morning towards the afternoon hours at Larnaca throughout the year. The maximum of daily reflected irradiation is about 6.5 MJ m-2 at Athalassa and about 7.5 MJ m-2 at Larnaca. The monthly mean daily values of albedo at Athalassa range between 0.175 to 0.224, while at Larnaca they are higher ranging from 0.198 to 0.239. As a result of the differences of the global and reflected radiation of the two sites, the net shortwave irradiation at Larnaca is slightly higher than that at Athalassa, almost throughout the year.
Keywords: Reflected irradiance; Global irradiance; Albedo; Clearness index; Statistical analysis; Cyprus